Revitalisasi Peran Masjid dalam Menguatkan Pendidikan Agama Islam di Desa Sukadono, Kabupaten Deli Serdang - Iswanto Ariga; Hadi Saputra Panggabean (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Mosques have long played a strategic role in shaping Muslim character through Islamic Religious Education (IRE). In many rural contexts, however, including Sukadono Village, Deli Serdang Regency, the educational function of mosques has gradually declined and become less responsive to community needs. This study addresses this gap by examining the current condition of mosque-based IRE in Sukadono, identifying the structural and socio-cultural constraints that hinder its implementation, and formulating revitalization strategies grounded in local needs and community participation. Employing a qualitative descriptive approach with a case study design, data were collected through participant observation, in-depth interviews, and document analysis. The data were analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing and verification. The findings reveal that limitations in human resources, program sustainability, and community engagement significantly affect the effectiveness of mosque-based education. This study argues that participatory, context-sensitive revitalization strategies can restore the mosque’s educational role and strengthen its relevance in rural settings. The novelty of this research lies in its participatory focus on rural mosques, offering a sustainable model for community-based Islamic education development.